Hak-Hak Anak dalam Pasal 54 UU No. 35 Tahun 2014 tentang Perlindungan Anak - Tang, Ahmad (JURNAL AL-QAYYIMAH, 2019)
This paper explores the rights of children in LAW No. 35 year 2014 on child protection. The results showed that child rights included; 1. The right to obtain protection from physical violence, which may result in injuries or injuries to children, such as hitting, persecuting, slapping, punching, kicking, pinching, pushing, wearing various objects or electric flows, bracing in space, movement Excessive physical, prohibiting urination, etc., 2. The right to obtain protection from psychic violence involves attitudes that are intended to be intimidating and persecuting, threatening or abusing authority, isolating and other causes that result in decreased confidence, increasing the sense of To act and be powerless. 3. The right to be protected againstsexual crimes in the form of improper sexual intercourse in an unusual and/or unnatural manner, the coercion of sexual intercourse with another person for commercial purposes and/or a particular purpose. Some forms of sexual violence that often occur in children are; Rape, sodomy, fornication, the sale of children for sexual services, sexual exploitation of children for prostitution, and the sexual exploitation of children through child marriage. 4. The right to protection from other crimes.